Gut inflammation is associated with structural spinal damage in axial spondyloarthritis – results from the observational SPARTAKUS cohort - Wallman, Johan Karlsson; Mogard, Elisabeth ; 0000-0002-5706-203X; Sagard, Jonas ; 0000-0001-7227-0665; Andréasson, Kristofer; Marsal, Jan ; 0000-0003-4808-0014; Inci, Fatih; Geijer, Mats; Olofsson, Tor; Lindqvist, Elisabet ; 0000-0002-9937-6352 (Arthritis Research and Therapy, 2025)
Background: In axial spondyloarthritis (axSpA), 5–10% of patients have comorbid inflammatory bowel disease (IBD). Beyond that, 50–60% display histologic inflammation in ileum/colon biopsies, and fecal calprotectin (F-calprotectin) is elevated in relation to healthy controls. Prior studies have shown such, often subclinical, gut inflammation in axSpA to be associated with more active disease, as measured by clinical indices as well as magnetic resonance imaging – both known risk factors for structural spinal damage development. In light of this, in the current study we aimed to examine whether gut inflammation, assessed by F-calprotectin, is associated with more structural spinal damage in axSpA. Methods: Patients with well-characterized non-radiographic or radiographic axSpA (nr-axSpA/r-axSpA; n = 76/152), according to ASAS or modified New York criteria, enrolled in a population-based cohort study in southern Sweden, were assessed for structural spinal damage (modified Stoke ankylosing spondylitis spinal score [mSASSS]) and gut inflammation (F-calprotectin). mSASSS values were compared between patients with normal (< 50 mg/kg), moderately elevated (50–149 mg/kg) or distinctly elevated (≥ 150 mg/kg) F-calprotectin, reflecting no/some/evident gut inflammation, respectively (one-way ANOVA). Moreover, logistic regression was applied to explore if elevated F-calprotectin (≥ 50 mg/kg) was associated with mSASSS values above the median, adjusted for sex, symptom duration, HLA-B27 status, smoking, CRP, NSAID and anti-TNF therapy. Analyses limited to r-axSpA were also performed. Results: In both axSpA patients overall and separately in r-axSpA, mSASSS distributions differed significantly between subjects with normal/moderately/distinctly elevated F-calprotectin, with more damage observed in those with higher F-calprotectin levels. Furthermore, elevated F-calprotectin (≥ 50 mg/kg) was associated with mSASSS values above the median, in both the entire axSpA group (adjusted odds ratio [OR] 2.2 [95%CI 1.1–4.2]); and in r-axSpA alone (adjusted OR 2.9 [1.2–7.1]). Conclusion: In the current study, the presence of gut inflammation, assessed by F-calprotectin, was cross-sectionally associated with more structural damage in the spine in patients with axSpA, even after adjustments for known risk factors for spinal damage. Prospective studies are, however, needed to investigate whether gut inflammation may be a predictor of spinal radiographic progression in axSpA.
Keywords: Ankylosing spondylitis; Calprotectin; Gut inflammation; Inflammatory bowel disease; Non-radiographic axial spondyloarthritis; Radiographic progression; Spondyloarthritis; Structural damage